2012
DOI: 10.1038/npre.2012.7053.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Soybean Oil, Protein and Amino Acid Residues in Soybean Seeds by High Resolution Nuclear Magnetic Resonance (NMRS) and Near Infrared (NIRS)

Abstract: A detailed account is here presented of our high resolution nuclear magnetic resonance (HR-NMR) and near infrared (NIR) calibration models, methodologies and validation procedures, together with a large number of composition analyses for soybean seeds. NIR calibrations were developed based on both HR-NMR and analytical chemistry reference data for oil and twelve amino acid residues in mature soybeans and soybean embryos. This is our first report of HR-NMR determinations of amino acid profiles of proteins from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Seed composition and morphological traits analyses. Seed composition traits were measured using the high-throughput near-infrared reflectance (NIR) method, which is now a common way of measuring seed composition traits in soybean 47,48 . The results of seed composition analyses showed that the seed oil accumulation in transgenic lines of DGAT1-11A-3, DGAT1-11B-1, and DGAT1-15A-5 were decreased by 10 mg/g (by 4.5%), 18 mg/g (8.3%), and 11 mg/g (5.3%), respectively, in comparison with the wild-type, cultivar Jack.…”
Section: Figurementioning
confidence: 99%
“…Seed composition and morphological traits analyses. Seed composition traits were measured using the high-throughput near-infrared reflectance (NIR) method, which is now a common way of measuring seed composition traits in soybean 47,48 . The results of seed composition analyses showed that the seed oil accumulation in transgenic lines of DGAT1-11A-3, DGAT1-11B-1, and DGAT1-15A-5 were decreased by 10 mg/g (by 4.5%), 18 mg/g (8.3%), and 11 mg/g (5.3%), respectively, in comparison with the wild-type, cultivar Jack.…”
Section: Figurementioning
confidence: 99%
“…The entire spectrum of absorbance was used to generate the partial least squares (PLS) model ( Figure S3 ) for the near infrared analyses. The PLS was calculated over the selected wavelength range of 1100 nm–2500 nm [ 21 , 34 ]. The near infrared spectra were pre-treated mathematically and derivatized.…”
Section: Resultsmentioning
confidence: 99%
“…NIR spectroscopy is based on the region of the electromagnetic spectrum between visible light and infrared radiation, occurring from approximately 780 nm to 2600 nm [ 21 ]. It involves changes in vibration energies of the molecular bonds O-H, C-H, C-O, and N-H when subjected to NIR frequencies, wherein bonds undergo vibrational stretching and bending [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NIR technology has been applied to predict oil per se and its quality in rapeseed, safflower, and soybean (Tajuddin et al, 2002;Kim et al, 2007;Patil et al, 2010;Rudolphi et al, 2012;Wittkop et al, 2012); fiber fractions in rapeseed (Wittkop et al, 2012); starch, protein, oil, amino acid composition and weight of individual grains in maize (Spielbauer et al, 2009;Tallada et al, 2009;Rosales et al, 2011); stover quality in maize (Melchinger et al, 1986); amino acid composition in soybean (Kovalenko et al, 2006); protein, starch and seed weight in intact seed in common bean (Hacisalihoglu et al, 2010); and for sensing moisture content of in-shell peanut (Sundaram et al, 2012). Baianu et al (2012) developed a high-resolution nuclear magnetic resonance and NIR models that they validated by estimating amino acid profiles of proteins from a large number of single and bulked soybean seeds, without protein extraction from the seed. Using partial least squares regression technique to analyze the NIR spectral data, they found that single soybean seed NIR spectra are broadly similar to those of bulk whole soybeans, with the exception of minor peaks, 950-1000 nm, in single soybean NIR spectra.…”
Section: Minerals From Plant Tissues or Grains Samplesmentioning
confidence: 99%